Palladacycle-catalyzed asymmetric intermolecular construction of chiral tertiary p-heterocycles by stepwise addition of H–P–H bonds to bis(enones) - Pullarkat, Sumod A. (2013)
A palladacycle-catalyzed diastereo- and enantioselective stepwise double hydrophosphination of bis(enones) with PhPH2 has been developed, allowing intermolecular construction of chiral tertiary bulky P-heterocycles in one pot in high yields. A catalytic cycle for the reaction is proposed as well.